Role of GABAA receptor depolarization-mediated VGCC activation in sevoflurane-induced cognitive impairment in neonatal mice - Zeng, Shuang; Zhu, Ruilou; Wang, Yangyang; Yang, Yitian; Li, Ningning; Fu, Ningning; Sun, Mingyang; Zhang, Jiaqiang (Frontiers in Cellular Neuroscience, 2022)
Background: Sevoflurane anesthesia induces depolarization of GABAA receptor leading to cognitive impairment in neonatal mice.Calcium accumulation in neurons can lead to neurotoxicity. VGCCs can increase the intracellular calcium concentration under the condition of isoflurane and hypoxia.The underlying mechanisms remain largely to be determined. Methods: Six day-old mice received anaesthesia with sevoflurane 3% for 2 h daily for 3 days. Y Maze,New Object Recognition Test,Barnes Maze Test,immunoassay, immunoblotting, Tunel Test and Golgi-Cox staining were used to assess cognition; Calcium concentration, inflammatory response, activation of GABAA receptors, expression of VGCCs, apoptosis and proliferation of hippocampal nerve cells in mice and HT22 cells. Results: Compared with the control group, the cognitive function of sevoflurane group mice was impaired.In sevoflurane group, the expression of Gabrb3 and Cav1.2 in hippocampal neurons increased(p<0.01), the concentration of calcium ion increased(p<0.01), the inflammatory reaction and apoptosis of neurons increased(p<0.01), the proliferation of neurons in DG area decreased (p<0.01)and the density of dendritic spines decreased(p<0.05).However, inhibition of Gabrb3 and Cav1.2 alleviated cognitive impairment and reduced neurotoxicity. Conclusions: Sevoflurane lead to VGCCs activated by inducing GABAA receptor depolarization, resulting in cognitive impairment.VGCCs activated leads to the increase of intracellular calcium concentration and inflammatory response, resulting in neurotoxicity and cognitive impairment.